New species and records of Pseudolanurgus (Coleoptera: Curculionidae, Scolytinae) from Tanzania and Madagascar - Jordal, Bjarte H. (Zootaxa, 2021)
The recently established genus Pseudolanurgus Jordal, 2021 included one species from Democratic Republic of the Congo and two from Madagascar. Two more species are here described as new to science: Pseudolanurgus mystax sp. nov. from the United Republic of Tanzania and Pseudolanurgus asperatus sp. nov. from Madagascar. A key to all five species is provided along with photos of all species.